2003
DOI: 10.1111/j.0963-1690.2003.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Chi and Organizational Creativity: A Case Study of Three Taiwanese Computer Firms

Abstract: The mechanisms of knowledge management include knowledge sharing, knowledge transformation and knowledge accumulation. In the corporate context, knowledge creation is of utmost importance for the promotion of competition within an organization. Knowledge creation in business corporations is most frequently done through sharing knowledge between members of a team. Therefore, how to promote the flow of 'Chi' in an organization to ensure the effectiveness of knowledge sharing becomes the key to successful knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…From an environmental perspective, creativity appears to be enhanced when the work place is borderless, as this facilitates interactions and free chatting among team members (Haner, 2005;Hong et al, 2003). Besides free chatting, formal forums appear to be necessary to effectively share knowledge and also promote creativity.…”
Section: Creativity Within Organizationsmentioning
confidence: 99%
“…From an environmental perspective, creativity appears to be enhanced when the work place is borderless, as this facilitates interactions and free chatting among team members (Haner, 2005;Hong et al, 2003). Besides free chatting, formal forums appear to be necessary to effectively share knowledge and also promote creativity.…”
Section: Creativity Within Organizationsmentioning
confidence: 99%
“…The process of creating a valuable, useful and different product within a complex social system that has not yet been revealed in organizational change and innovation is defined as organizational creativity (Jeong and Shin, 2019). Hong et al (2003) found that the concept of creativity is positively affected in the work environment where employees can interact easily and information flow is fast. Hu et al (2013) state that maintaining an organizational climate that supports change and encourages creativity is a fundamental goal for leaders as the environment in which organizations operate changes and becomes increasingly competitive.…”
Section: Organizational Creativitymentioning
confidence: 99%
“…This area was kept in the alternative based, for instance, in the study developed by Hong et al (2003), which states that an office should have both working and meeting spaces and should support informal knowledge-sharing, as well as the suggestion of taking into special consideration amenity spaces (e.g., relaxation rooms, gardens, and cafes) made by Tompkins et al (2010).…”
Section: Spaces Determinationmentioning
confidence: 99%
“…More so, many experiments on physical environments for creativity highlight the great importance of meetings among people, mainly face-to-face interaction-but also virtual encounters-as the most important activity in order to achieve creative insights (Tompkins, White, Bozer, & Tanchoco, 2010;Oksanen & Ståhle, 2013). The sharing of tacit knowledge between workers is the main core for developing a facility that focus on creative processes (Hong, Hwang, & Lin, 2003). Also of relevance is the availability of information sources, presentation devices, and information systems that might support the knowledge sharing and the knowledge management (Kristensen, 2004;Magadley & Birdi, 2009).…”
mentioning
confidence: 99%